Algebra

Please help me solve:

[SQRT(x)]=-2
1.
[SQRT(2x2 - 1)]=x

  1. 0
  2. 0
  3. 1
asked by George
  1. [SQRT(x)]=-2
    has no solution since by definition √ gives only positive result.

    for verification graph f(x) = √x + 2
    it never touches or crosses the x-axis

    for the second, I assume you mean
    √(2x^2-1) = x
    square both sides
    2x^2-1 = x^2
    x^2 = 1
    x = ±1
    but since we squared, both answers must be verfied.
    if x=1
    LS = √(2-1) = 1
    RS = 1, so it works

    if x=-1
    LS = √(2-1) = 1
    RS = -1 , does not work

    so x = 1

    1. 0
    2. 0
    posted by Reiny

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine
  2. Algebra 2

    Operations with Complex Numbers Simplify. 1. sqrt(-144) 2. sqrt(-64x^4) 3. sqrt(-13)*sqrt(-26) 4. (-2i)(-6i)(4i) 5. i13 6. i38 7. (5 – 2i) + (4 + 4i) 8. (3 – 4i) – (1 – 4i) 9. (3 + 4i)(3 – 4i) 10. (6 – 2i)(1 + i) 11.
  3. Math:)

    A person is on the outer edge of a carousel with a radius of 20 feet that is rotating counterclockwise around a point that is centered at the origin. What is the exact value of the position of the rider after the carousel rotates
  4. Inequality

    When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution? Is it (+sqrt(3),-sqrt(3)) or (-infinity, sqrt(3))? Why? Thanks. So would this work? abs x < ( sqrt 3 ) or - sqrt 3
  5. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2,
  6. Algebra

    Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now
  7. some algebra help (radicals)

    I hope I am writing this down right.. I am trying to do some practice questions to learn 10^5 (sqrt)2y - 4^5 (sqrt)2y I am trying to figure out how to solve this They gave us some answers to choose from, but I am clueless on how
  8. Math/Calculus

    Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else? Thanks. y''+4y'+6y=0, y(0)=2, y'(0)=4 r^2+4r+6=0, r=(-4 +/- sqrt(16-4(1)(6))/2 r=-2 +/- sqrt(2)*i , alpha
  9. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which
  10. Algebra 2: Radicals URGENT!!

    Could some kind, saintly soul help me solve this problem? Simplify: 8w sqrt(48w^5) - x^2 sqrt(3xw^2) . . =8w(√16)(√3)(√w^4)(√w) - x^2(√3)(√x)(√w^2) =32w^3(√3w) - wx^2(√3x) not much of a "simplification" really 8w
  11. Calculus - Second Order Differential Equations

    Posted by COFFEE on Monday, July 9, 2007 at 9:10pm. download mp3 free instrumental remix Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8))

More Similar Questions